The medical profession, societal demands and developing legal standards - Jahn Kassim, Puteri Nemie; Jahn Kassim, Puteri Shanaz (LexisNexis, 2014)
The medical profession has, in the past, been accorded an unparalleled level of deference. It was perceived as a profession that can do no wrong and had considerable powers over patients as well as regulating its own medical practice. However, the growth of the medical profession as a public institution and the commercialisation of medical practice have shaped the contours and behaviour of the society in demanding greater obligations and accountability on the part of the medical profession. The increasing awareness amongst the society on medico-legal issues as well as the growth of consumerist attitude towards the provision of medical services has caused the medical profession to be subjected to vociferous criticism if it does not meet the rising expectations of the society. Substandard services have not been well tolerated and paternalistic approaches in medical treatment are considered to be outmoded and inappropriate. Judicial interventions in medical practice have created more rights for patients and consequently, corresponding legal duties for the medical profession to uphold. In the contemporary healthcare setting, the medical profession will not be able to provide infallible services without attaining the highest standards of professionalism and knowledge of the legal standards which they have to adhere. As the medical profession’s obligations transgressed into an environment dominated by societal needs and collectivist cultures, the ideals of professionalism not only require them to have the necessary expertise, dedication, respect, compassion, empathy, honesty, altruism, responsibility, integrity, self-improvement and accountability but also to adhere to the demands of law and highest ethical standards.